Understanding Traditional Culinary Engagement: The Impact of Income Levels, Lifestyle Patterns, and Sensory Branding - Ari Arisman; Isyana Rahayu; Mohamad Herdi Faizal; Teuku Dhani Al Ramdhani; Viska Putria Ananda (Universitas Mercu Buana, 2026)
The study aims to address the limited empirical studies that simultaneously examine economic, psychographic, and sensory factors in shaping traditional culinary experiences, with a focus on Nasi Tutug Oncom in Tasikmalaya.Objectives: The study examines the influence of income level, lifestyle, and sensory branding on the culinary consumption experience of traditional food consumers.Methodology: The study used a quantitative survey approach using an online questionnaire that was sent to 272 participants that were selected using Cochran's formula. Data were analyzed using SPSS, which included validity, reliability, linearity, and multiple regression analysis.Findings: The results suggest that while lifestyle has no discernible impact, income level and sensory branding have a positive and considerable impact on the gastronomic consumption experience. The F-test shows that the model fits the data well, suggesting that the independent variables together account for the variation in gastronomic consuming experience.Conclusion: The study concludes that while lifestyle has little bearing on traditional culinary experiences, financial ability and sensory stimuli are important factors in enhancing them.